Evaluation of antimicrobial, cytotoxic and chemopreventive activities of carvone and its derivatives - Isabela Jacob Moro; Gabrielle Demmany Gualberto Alexandre Gondo; Elaíse Gonçalves Pierri; Rosemeire Cristina Linharis Rodrigues Pietro; Christiane Pienna Soares; Damião Pergentino de Sousa; André Gonzaga dos Santos (Universidade de São Paulo, 2018)
ABSTRACT Considering the reported activity of carvone in the literature, this study aimed to evaluate the antimicrobial, cytotoxic and chemopreventive activities of (+)- and (-)-carvone, (+)- and (-)- hydroxydihydrocarvone and α,β-epoxycarvone. (+)-Hydroxydihydrocarvone (HC+), (-)-hydroxydihydrocarvone (HC-) and α,β-epoxycarvone (EP) were obtained by synthesis using (+)-carvone (C+) or (-)-carvone (C-) as precursors. The antifungal activity (MIC and MFC) were evaluated against Candida parapsilosis, C. tropicalis, C. krusei and C. albicans and the antibacterial activity (MIC and MBC) against Escherichia coli and Staphylococcus aureus. The cytotoxicity assays were performed with human cancer cell lines HepG-2 and SiHa and the normal strain MRC-5 through sulphorrodamine B assay. Chemoprevention was evaluated through quinone reductase assay. Our results showed no cytotoxicity on tumor and normal cell lines and no induction of the quinone reductase enzyme. C- and HC- presented activity against E. coli. All compounds presented weak antifungal activity against C. tropicalis and C. parapsilosis. EP and C+ showed moderate activity against C. krusei. Results suggest the potential use of carvones and its derivatives as antifungal agents against Candida yeasts. The absence of cytotoxicity in cell lines indicates safety in the use of these compounds.